2013
DOI: 10.1589/jpts.25.521
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the Short- and Long-term Changes in Exercise Habit and Body Composition, Blood Pressure and Health-related Quality of Life among Health Program Participants

Abstract: Abstract.[Purpose] The purpose of this study was to investigate the relationships between change in exercise habit and changes in body composition, blood pressure and health-related quality of life among participants in a health-guidance program with no exercise habit.[Subjects] The subjects were 3 males and 12 females (mean age, 65.4 years).[Methods] The intervention was a 6-month exercise-and nutritional-guidance program. Outcome measures were body composition, blood pressure, and health-related quality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The change in cortisol level depends mainly upon the type of exercise. Decreased levels of cortisol were reported in individuals performing both low intensity 14 ) , and acute exercise training 15 , 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The change in cortisol level depends mainly upon the type of exercise. Decreased levels of cortisol were reported in individuals performing both low intensity 14 ) , and acute exercise training 15 , 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…To represent the route recommendation mathematically, considering 57 pairs of manually specified start q 0 and end points q e , the system generates the walking trajectory group S = {s(q 0,i , mq e,i )}(i ∈ [1,57]) to simulate the walking motion by DHM on each trajectory. The tripping rate is calculated for the young (sub.…”
Section: ) Selection Of the Start And End Positionsmentioning
confidence: 99%
“…Health-care workers and medical experts recommend walking as a critical determinant for alleviating the onset of lifestyle-related diseases. Knowing the value of mobility for a better Quality of Life (QoL) can increase motivation to perform at-home exercises [1]. In Japan, walking has been embraced by individuals of all age groups but is especially popular among those aged 50 years and the elderly [2].…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that physical inactivity causes 6% of the burden of disease from coronary heart disease, 7% of that from type 2 diabetes, and 10% of that from breast cancer and colon cancer and that elimination of physical inactivity would increase the life expectancy of the world’s population by 0.68 years 7 ) . In addition, some recent studies have found that physical activity and exercise are associated with cognitive function 8 , 9 , 10 ) , mental health 11 ) , and health-related quality of life 12 , 13 ) . Therefore, it is important to maintain regular physical activity and exercise habits.…”
Section: Introductionmentioning
confidence: 99%